Study on physical properties of four pH responsive Spodoptera exigua multiple nucleopolyhedrovirus (SeMNPV) microcapsules as controlled release carriers - Meng Luo; Juntao Lin; Xinhua Zhou; Xia Pu (Scientific Reports, 2022)
Abstract This study provides a promising controlled release form of nuclear polyhedrosis virus (NPV) for targeted control of lepidopteran pests. However, the application of NPV is limited due to its sensitivity to UV inactivation. This study investigated the anti-UV properties of microcapsules of SeMNPV occlusion bodies (OBs) encapsulated by calcium alginate (CA), and also the influence of the modification of CA by chitosan (CS), whey protein (WP), and polydopamine (PDA). These capsules were used to deliver, in a controlled release manner virions under alkaline pH conditions. Characterization of the structure, morphology, particle size, encapsulation efficiency, contact angle, insecticidal activity, UV resistance and in vitro release of the microcapsules was conducted. The modified microcapsules had better sphericity, and were devoid of SeMNPV OBs on the surface. The encapsulation rate was 84.76 ± 0.59%. PDA@CA-NPV had the highest wettability and the contact angle was 74.51 ± 0.53°. The 50% lethal concentration values (LC50) of CA-NPV, CS@CA-NPV, WP@CA-NPV and PDA@CA-NPV were 11.5, 10.7, 10.5 and 1.2 times that of SeMNPV OBs alone. The modified microcapsules all improved the anti-UV performance of the virus, and PDA@CA-NPV was the most UV-resistant. Using qPCR, it was observed that under alkaline conditions, a large number of virions were released from PDA@CA-NPV, CA-NPV and SeMNPV OBs. Microencapsulated virus under alkaline conditions did not change the release pattern of virions.